ANALYSIS OF SESAME PRODUCTION AMONG INDIGENOUS AND NON-INDIGENOUS FARMERS IN YAGBA EAST, KOGI STATE, NIGERIA (American International Journal of Agricultural Studies, 2023)
Sesame is one of the oil crops with high economic value. Its production is becoming more pronounced in many parts of the world and gaining more ground among farmers in Nigeria. The study analyzed sesame production among indigenous and non-indigenous farmers in Yagba East, Nigeria. This study employed a Two-stage sampling technique in collecting primary data from one hundred and twenty respondents. It is a comparative study with specific objectives embedded. The data collected were analyzed using Descriptive statistics, t-test, Gross margin analysis, and a 4.0-point Likert scale. The results show that the majority (58.33%) of indigenous farmers were young, while (65.00%) of non-indigenous farmers were middle age. Also, most respondents were married (65.00%, 81.67%) indigenous and non-indigenous farmers. The average total revenue (N370,452.50, N548,712.40) per hectare accrued to indigenous and non-indigenous farmers, respectively. The average total costs the indigenous and non-indigenous farmers expended were (N70,152.28, N84,408.18) per hectare, respectively. The findings showed (5.28, 6.50) as benefit-cost ratio (BCR) for the indigenous and non-indigenous farmers, respectively. The results revealed that the high cost of fertilizer (mean score=3.38, 3.88), lack of improved seed (mean score=3.23, 2.53), high transportation cost (mean score=3.25, 3.52), and access to credit (mean score= of 3.43, 3.42) were serious constraints confronting both the indigenous and non-indigenous farmers respectively. Therefore, good road construction is needed through self-help or government intervention for effective transportation of inputs and output, extension visit is paramount, and farmers' resources should be pooled together to enhance farmers' access to adequate finances.JEL Classification Codes: G32.